2020
DOI: 10.5664/jcsm.8526
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of esmirtazapine in adult outpatients with chronic primary insomnia: a randomized, double-blind placebo-controlled study and open-label extension

Abstract: Study Objectives: Esmirtazapine (1.5-4.5 mg) has demonstrated short-term sleep-promoting effects in nonelderly outpatients with chronic insomnia. This phase 3, randomized, double-blind study (NCT00631657) and its open-label extension (NCT00750919) investigated efficacy and safety of long-term esmirtazapine treatment in adult outpatients with chronic insomnia. Methods: Participants were randomized to receive esmirtazapine 4.5 mg or placebo for 6 months; those receiving esmirtazapine were then rerandomized to es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…Another randomized placebo-controlled trial comprised of 457 adults with chronic insomnia studied the effects of esmirtazapine 4.5 mg or placebo for 6 months followed by a 7-day discontinuation period [ 94 ]. Following the treatment period, the esmirtazapine group was double-blind re-randomized 1:2 to continue esmirtazapine ( n = 65) or abruptly switch to placebo ( n = 137).…”
Section: Resultsmentioning
confidence: 99%
“…Another randomized placebo-controlled trial comprised of 457 adults with chronic insomnia studied the effects of esmirtazapine 4.5 mg or placebo for 6 months followed by a 7-day discontinuation period [ 94 ]. Following the treatment period, the esmirtazapine group was double-blind re-randomized 1:2 to continue esmirtazapine ( n = 65) or abruptly switch to placebo ( n = 137).…”
Section: Resultsmentioning
confidence: 99%
“…A series of double‐blind, placebo‐controlled studies has been carried out with the S‐isomer of mirtazapine, esmirtazapine, dosed from 1.5 to 4.5 mg, demonstrating robust efficacy for both sleep onset and maintenance difficulties as well as a relatively favourable safety profile in the treatment of patients with insomnia (Ivgy‐May, Roth et al, 2015; Ivgy‐May, Ruwe et al, 2015; Ivgy‐May et al, 2020). However, these studies are of uncertain relevance to the use of racemic mirtazapine because when dosing the racemate, the blood levels of the R‐isomer are higher than the S‐isomer and the R‐isomer has a longer elimination half‐life.…”
Section: Evidence‐based Review Of Mechanism Of Action‐based Clinical ...mentioning
confidence: 99%
“…
Confirmation that 5-hydroxytryptamine receptor 2A/2C antagonists such as esmirtazapine work for insomnia, based on 2009-2010 trials, is welcome news. 1 Research has shown that 5-hydroxytryptamine receptor 2A/2C antagonists such as mirtazapine and trazodone have a long history of use for insomnia, 2-4 but large double-blind insomnia studies have been lacking. Ivgy-May et al 1 do make some assertions that require caveats.The authors state without supporting data or references that esmirtazapine has a shorter half-life than the racemic mixture.
…”
mentioning
confidence: 99%